A comparative study of social inequalities in education as an effect of Covid-19 pandemic: A case of schools in Saudi Arabia and Kenya (International Journal of Scientific Research and Management (IJSRM), 2022)
The Coronavirus epidemic is a major source of concern for global education systems and their ability to provide equity in education. Hundreds of countries closed schools during the Covid-19 in its first year to contain the mass spread of the virus. Over one billion students were denied an education as a result of Covid-19 school closures. This study compares the social inequalities experienced in schools in Kenya and Saudi Arabia following the outbreak of Covid-19. An extensive questionnaire on data collection methods was completed by educators, learners, and parents from public schools in these two countries. The statistics were calculated using the SPSS program while qualitative data was analyzed thematically. Covid-19 had a significant impact on the time used for learning, the content learned, and the quality of learning that was experienced in the sampled countries. The findings show that during the Coronary Syndrome outbreak, many learners and educators relied on technology to access continuing education. Unfortunately, inadequate infrastructures such as lack of network availability, structure, and proper policies hampered virtual education and expanded the social inequality between learners of the two sampled countries. The findings of this study highlight the devastating impact Covid-19 had on the education sector: schools, educators, learners, and parents. In brief, the success of continuity in education depended on the government policymaking and implementation that geared towards equity in the provision of education.